Status Gizi Terhadap Usia Menarche Pada Remaja - Achmad Setya Roswendi; Haifa Khoirunisa Damayanti (Yayasan Healing and Healthcare Education, 2023)
Background: Judging from the results of the World Health Organization (WHO) it is stated that around 95% of women experience menarche at the age of 12 years but now it has shifted to a younger age, namely the age of 10-11 years, which is around 24.92%, while in Indonesia it is around 25.3%. women have menarche by 12 years. One of the factors that affect the age of menarche is nutritional status because this plays an important role in determining the age of menarche and the complaints felt at the time of menarche. Objective: This study was to identify the relationship between nutritional status and age of menarche in adolescents. Methods: This study uses a research design with the Literature Review method using a systematic review approach. Through the steps in PRISMA, with media searches using Science Direct=549, Pubmed=8, and Google Scholar=2,700 from 2016-2021. Five journals were obtained which were then analyzed using The Joana Briggs Institute (JBI) Cross Sectional and searched for their relationship and used the Plagiarsm Checker X application to check for plagiarism. Results: Research in the four journals showed that there was a relationship between nutritional status and age at menarche, and 1 journal showed that there was a relationship between body mass index. Suggestion: The results of the literature review are expected to provide education to adolescents in terms of consuming good intake, one of which is for reproductive health.